Risk and Cost Analysis Study Occupational Health and Safety (K3) On Passenger Terminal Building Works New Mentawai Airport Development Project - Ranatika Purwayudhaningsari; Wateno Oetomo; Hanie Teki Tjendani; Ony Frengky Rumihin (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2023)
To provide adequate and quality air transportation facilities and infrastructure by developing and maintaining a sustainable air transport infrastructure, it is ?required attention to occupational safety and health risk factors. These factors need to be analyzed in order to achieve zero accidents in the implementation process. This study aims to identify OHS risk factors, determine the highest OHS risk factors and then prepare a Construction Safety Plan (RKK) based on the highest OHS risk factors in The Terminal Building Construction Of The New Mentawai Airport Development Project, to determine the control of these risks. Interviews, and questionnaires as well as the results of previous studies, were collected to determine the risk factors for OSH. The Analytical Hierarchy Process method was applied to determine the highest risk factor which was carried out by compiling the AHP questionnaire and inputting it in the Expert Choice application. The Construction Safety Plan is prepared after the AHP analysis, in which the required OHS costs are also known. There are 4 aspects of risk factors: Workers Aspect, Management Aspect, Equipment Aspect, and the Environment Aspect with 24 risk factors. The risk factor for worker burnout, which is part of the worker aspect and is carried out in structural work, is the highest. Furthermore, the Construction Safety Plan (RKK) is prepared based on the Regulation of the Minister of Public Works of the Republic of Indonesia Number 10 of 2021 concerning Guidelines for Construction Safety Management Systems with an OHS cost of this construction IDR 698,250,000.00. This study emphasizes the importance of paying attention to risk factors, namely the burnout condition of workers, which is rarely considered in the implementation of construction work.